Socially controlled male‐to‐female sex reversal in the protogynous orange‐spotted grouper, Epinephelus coioides. Issue 3 (20th February 2019) - Chen, Jiaxing; Xiao, Ling; Peng, Cheng; Ye, Zhifeng; Wang, Dengdong; Yang, Yuqing; Zhang, Haifa; Zhao, Mi; Li, Shuisheng; Lin, Haoran; Zhang, Yong
Abstract : Socially controlled sex change in teleosts is a dramatic example of adaptive reproductive plasticity. In many cases, the occurrence of sex change is triggered by a change in the social context, such as the disappearance of the dominant individual. The orange‐spotted grouper Epinephelus coioides is a typical protogynous hermaphrodite fish that changes sex from female to male and remains male throughout its life span. In this study, male‐to‐female sex reversal in male Epinephelus coioides was successfully induced by social isolation. The body length and mass, gonadal change, serum sex steroid hormone levels and sex‐related gene expression patterns during the process of socially controlled male‐to‐female sex reversal in E. coioides were systematically examined. This report investigates the physiological mechanisms of the socially controlled male‐to‐female sex reversal process in a protogynous hermaphrodite grouper species. The results enable us to study the physiological control of sex change, not only from female to male, but also from male to female.